Time to recovery from haemodialysis : location, intensity and beyond. Issue 12 (December 2016) - Jayanti, Anuradha; Foden, Philip; Morris, Julie; Brenchley, Paul; Mitra, Sandip; ,
Abstract: Introduction: Prolonged recovery time (RT) affects patient's quality‐of‐life adversely. Shorter dialysis RT in home haemodialysis (HHD) noted in observational studies has been attributed to intensive dialysis regimens. Home patients adopt different haemodialysis (HD) schedules. There is insufficient literature on RT in HHD patients receiving different HD schedules. Methods: Data was prospectively collected for BASIC‐HHD study, a multicentre study of home and hospital HD across five tertiary centres in the UK. Two hundred and eighty‐eight patients answered the question, 'how long does it take for you to recover from a haemodialysis session?' Ninety‐one patients (31.8%) of study population performed HHD. Participants completed neuropsychometric tests and depression and anxiety screening inventories. Results: Recovery time is longest amongst 'in‐centre' HD recipients (Mean 193 min; SD 295.37) and significantly higher than the mean RT of home HD recipients (Mean 67.3 min; SD 86.8). Within the home setting, RT was not significantly different between the intensive HD and conventional HD (67.8 vs 66.5 min; P > 0.05) groups but higher residual urine volumes in the standard home group had significantly shorter RT. Location of HD, not intensity, remained significant ( P = 0.001) in the unadjusted and adjusted multivariable analysis. Longer RT was associated with female gender, unemployed or retired 'work' status, 'non‐white' ethnicity, lower predialysis systolic blood pressure and greater depression screening score. Conclusions: Home‐based HD and higher residual urine volumes are significantly associated with shorter RT. This home advantage for RT may be sustained by preserving residual renal function (in early stages) and increasing HD intensity (in later stages) of dialysis therapy. Summary at a Glance: This manuscript details interesting insights into potential determinants of recovery time after haemodialysis drawn from a large longitudinal study in the UK. The results are relevant to the audience of Nephrology.